Motivating English Language Use by using the Benefits of Technology - Rivera Barreto, Adriana Maritza (GIST – Education and Learning Research Journal, 2018)
This paper shares the results of a small-scale research project focused on using technology to motivate the use of English. Tenth semester students from a University in Tunja was the target group to develop the project. It also had as an objective to promote a virtual learning environment to boost English as a foreign language. A field diary, an online forum, a survey, and students’ artifacts were used to gather information in this action research study. Findings revealed two categories, firstly, Collaborative work to instill motivation which explains why students tend to work better while working in groups and secondly The use of technology to enhance language learning where it is described how the use of technology makes students more confident to learn English.